Development of a Project Module for Strengthening Pancasila Student Profiles Containing Local Wisdom at SDN 6 Pempatan - Sukawana, I Wayan; Numertayasa, I Wayan; Astuti, Ni Putu Eni (Universitas Nusantara PGRI Kediri, 2024)
This study aims to determine the needs of educators and students in implementing the Pancasila Student Profile Strengthening Project activities, as well as the prototype and results of the validity test of the Pancasila Student Profile Strengthening Project module containing Local Wisdom. This study uses quantitative descriptive methods and descriptive statistics with a development research design to the product revision stage. There are 5 stages in this research design, starting from the potential and problem stages, data collection, product preparation, product validation, product revision from the validation results. The subjects of this study were educators and students of grade IV at SD N 6 Pempatan with the object of development in the form of the Pancasila Student Profile Strengthening Project Module containing Local Wisdom. The validation carried out by experts came from ITP Markandeya Bali Lecturers and Grade IV Homeroom Teachers at SD N 6 Pempatan, the validation of the Module was analyzed with descriptive statistics using a Likert scale. The module design was approved with several revisions, including adjusting the cover color, font type on the cover, adding a cover to the student worksheet (LKPD) that needed to be revised. The results obtained in the development research of the Pancasila Student Profile Strengthening Project Module Containing Local Wisdom are categorized as very valid from the results of the expert validation test with an average score of 131 from the interval scale that has been set. The difference between this development research and previous development research can be seen from the contents of the developed module, resulting in a difference in the module validation score. This is influenced by the module validation standards that are adjusted to the curriculum used.